Kontribusi Imam al-RÃ¢fiâÃ® dan Imam al-NawawÃ® dalam Penataan Keragaman Pendapat Hukum Mazhab ShÃ¢fiâÃ® - Saleh, Abdul MunÃ¢Â€Â™im (ISLAMICA: Jurnal Studi Keislaman, 2013)
The diversity of legal opinions in the ShÃ¢fiâÃ® school of thought (madhhab), in the form of old opinion (qawl qadÃ®m) and new opinion (qawl jadÃ®d) and the ijtihÃ¢d activities that pertained Â to some centuries after the passing away of al-ShÃ¢fiâÃ®, has brought this madhhab into encounter with serious problems in selecting the law. In such a situation, al-RÃ¢fiâÃ® and al-NawawÃ® came into the fore as muharrir (selector) to cope with this uncertainty. This research tries to analyze all scientific activities of the two scholars using the theory of tarjÃ®h. This research found out that they attempted to establish a legal certainty in the ShÃ¢fiâÃ® school of law through the making of new mixed system of tarjÃ®h to ensure which opinions deserve to be regarded as valid from the viewpoint of ShÃ¢fiâÃ® madhhab. This achievement contributes to the enrichment of ShÃ¢fiâÃ® madhhab as a legal school consisting of a great variety of legal opinions that equips itself with procedures of selection used as norms of everyday life.